Overwhelming response to APB's MUET super workshop / Norasyikin Abdul Malik - Abdul Malik, Norasyikin (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A total of 493 UiTM diploma students from Seri Iskandar and Tapah participated in Good English Language Learner (GELL): Malaysian University English Test (MUET) Band 6 Super Seminar organized by the Academy of Language Studies, UiTM Perak Branch. 257 students from UiTM Seri Iskandar attended the one-day workshop on September 22, 2018, while another 236 from UiTM Tapah attended two and a half-day workshop sessions on 21 and 28 September 2018. They were provided with compre-hensive notes, updated past year paper samples and meals at the workshop.